Pathogenesis of peritoneal drain complications; a case report of evolving adnexal evisceration following difficult retrieval of a retained peritoneal drain - John Imaralu; Funmilayo Oguntade; Chimaobi Nwankpa; Olumuyiwa Adelowo (Babcock University Medical Journal, 2022)
Background: Intra-peritoneal drainage dates back to the time of Hippocrates when long bone tissue, metal, and glass tubes were employed. The benefit of routine intra-peritoneal drainage however remains debatable in contemporary times. Retained drains may be outward manifestations of more sinister or latent complications and how an entrapped surgical drain is removed, may determine the occurrence of further complications.